Influence of spin orbit splitting and satellite transitions on nickel soft X‐ray optical properties near its L2, 3 absorption edge region. (20th October 2020) - Kiranjot,; Modi, Mohammed H.; Gupta, Raj Kumar; Sinha, Mangalika; Yadav, Praveen Kumar
Abstract : Experimentally obtained optical constants of the nickel near L ‐edge energy region show signatures of different excitations which are absent in the available databases. These excitations are explained using charge transfer effects and core‐hole interactions in valence and core excited states. Abstract : Transition elements exhibit strong correlations and configuration interactions between core and valence excited states, which give rise to different excitations inside materials. Nickel exhibits satellite features in its emission and absorption spectra. Effects of such transitions on the optical constants of nickel have not been reported earlier and the available database of Henke et al. does not represent such fine features. In this study, the optical behaviour of ion beam sputter deposited Ni thin film near the L 2, 3 ‐edge region is investigated using reflection spectroscopy techniques, and distinct signatures of various transitions are observed. The soft X‐ray reflectivity measurements in the 500–1500 eV photon energy region are performed using the soft X‐ray reflectivity beamline at the Indus‐2 synchrotron radiation source. Kramers–Kronig analysis of the measured reflectivity data exhibit features corresponding to spin orbital splitting and satellite transitions in the real and imaginary part of the refractive index (refraction and absorption spectra). Details of fine features observed in the optical spectra are discussed. To the best of our knowledge, this is the first study reporting fine features in the measured optical spectra of Ni near its L 2, 3 ‐edge region.